Pengaruh Perubahan Kebijakan Organisasi Terhadap Sikap Resistensi Pada Karyawan - Nazmah Nazmah (Publikasi Indonesia, 2022)
Change is an important thing for the company or organization as well as the employees themselves to be able to advance the organization. However, resistance in the change process can be a barrier in advancing the organization itself through several factors. This study aims to examine whether there is an effect of changing organizational policies on employee resistance attitudes. In research using quantitative methods and using questionnaire as a measuring tool. The scale used in questionnaire and changes in company policy uses a Likert scale with 4 choices of statements. Data processing is carried out using a computer system with the SPSS program. Data were collected from 105 scales distributed to permanent employees. Based on the results of the study, it is known that there is a significant influence between employee resistance attitudes to changes in organizational (F count = 80.278, p <0.05). From this research, it is also known that changes in organizational policies have contributed to the attitude of resistance in employees of PT. SEPCO&M Medan is 43.8% and 56.2% is influenced by other factors.